2016
DOI: 10.3324/haematol.2016.142976
|View full text |Cite
|
Sign up to set email alerts
|

Targeted positron emission tomography imaging of CXCR4 expression in patients with acute myeloid leukemia

Abstract: A cute myeloid leukemia originates from leukemia-initiating cells that reside in the protective bone marrow niche. CXCR4/CXCL12 interaction is crucially involved in recruitment and retention of leukemia-initiating cells within this niche. Various drugs targeting this pathway have entered clinical trials. To evaluate CXCR4 imaging in acute myeloid leukemia, we first tested CXCR4 expression in patient-derived primary blasts. Flow cytometry revealed that high blast counts in patients with acute myeloid leukemia c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 48 publications
2
46
0
3
Order By: Relevance
“…Because of the successful development of a radiolabeled CXCR4 ligand ( 68 Ga-pentixafor), it is now possible to visualize CXCR4 expression in vivo by means of PET imaging (6,7). Several proof-of-concept studies have shown the potential of the PET tracer 68 Ga-pentixafor to visualize CXCR4-positive tumors, with a specific applicability for patients with hematologic diseases such as non-Hodgkin lymphoma (8), multiple myeloma (9,10), and acute leukemia (11).…”
mentioning
confidence: 99%
“…Because of the successful development of a radiolabeled CXCR4 ligand ( 68 Ga-pentixafor), it is now possible to visualize CXCR4 expression in vivo by means of PET imaging (6,7). Several proof-of-concept studies have shown the potential of the PET tracer 68 Ga-pentixafor to visualize CXCR4-positive tumors, with a specific applicability for patients with hematologic diseases such as non-Hodgkin lymphoma (8), multiple myeloma (9,10), and acute leukemia (11).…”
mentioning
confidence: 99%
“…Animal studies were performed in agreement with the Guide for Care and Use of Laboratory Animals published by the US National Institutes of Health (NIH Publication n. 85-23, revised 1996), in compliance with the German law on the protection of animals, and with the approval of the regional authorities responsible (Regierung von Oberbayern). The in-vivo experiments were performed as published previously (Herhaus et al, 2016). Briefly, Seraphine-TP53wt, Seraphine-p53ko and Raji cell lines were infected in vitro with shNT or shMDM4 aiming at > 80% transduction efficiency.…”
Section: Methodsmentioning
confidence: 99%
“…To evaluate the potential of MDM4 as a therapeutic target in TP53wt BL in vivo, we determined the effect of MDM4 silencing on tumor growth in a mouse xenograft model. After transduction, cell lines representing TP53wt (Seraphine), TP53ko (Serphine-TP53ko) and TP53mut (Raji) were injected subcutaneously into the flanks of immunodeficient mice (Herhaus et al, 2016). To quantify tumor formation and dynamic growth, we measured fludeoxyglucose (FDG) uptake in positron emission tomography (PET).…”
Section: Mdm4 Is a Therapeutic Target In Tp53wt Blmentioning
confidence: 99%
“…85-23, revised 1996), in compliance with the German law on the protection of animals, and with the approval of the regional authorities responsible (Regierung von Oberbayern). The in vivo experiments were performed as published previously (23). Briefly, Seraphine-TP53wt, Seraphine-TP53ko, and Raji cell lines were infected in vitro with shNT or shMDM4 aiming at >80% transduction efficiency.…”
Section: Xenograft Modelmentioning
confidence: 99%
“…To evaluate the potential of MDM4 as a therapeutic target in TP53wt Burkitt lymphoma in vivo, we determined the effect of MDM4 silencing on tumor growth in a mouse xenograft model. After transduction, cell lines representing TP53wt (Seraphine), TP53ko (Seraphine-TP53ko) and TP53mut (Raji) were injected subcutaneously into the flanks of immunodeficient mice (23). To quantify tumor formation and dynamic growth, we measured fludeoxyglucose (FDG) uptake in positron emission tomography (PET).…”
Section: Mdm4 Is a Therapeutic Target In Tp53wt Burkitt Lymphomamentioning
confidence: 99%